The new Blackwell companion to the city - Bridge, Gary.; Watson, Sophie (Malden, MA : Wiley-Blackwell, 2011)
"Drawing together leading scholars from a variety of academic disciplines, this collection reports the leading edge of research and analysis into the contemporary urban condition. With more than half of the world's population living in urban environments, cities are places of huge complexity and diversity and the processes and structures that bind them together reach out across the globe. This volume considers the state of the city and contemporary urbanisation from a range of intellectual and international perspectives. Whilst considering established themes, such as urban divisions and differences, publics and cultures, politics and planning, the New Blackwell Companion to the City also addresses new debates on subjects like materiality, mobilities, and environment. Incorporating international examples, this book explores the economic, social, cultural, environmental and political issues that flow from and within the modern city"--
Part I. City materialities -- part II. City mobilities -- part III. City affect -- part IV. City publics and cultures -- part V. City divisions and differences -- part VI. City politics and planning.
Revised edition of: A companion to the city, 2000.
Includes bibliographical references and index.
Print version record.
Keywords: Cities and towns; Cities and towns -- Cross-cultural studies; SOCIAL SCIENCE -- Sociology -- Urban; Cities and towns; Electronic books; Cross-cultural studies